(3GdYhdeI GdeGdjI h Gdfeh GdGbJUGOj (B/s - (3MeRI, MSf cQjes ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2011)
(3eaghe GdYhdeI GdeGdjI h Gdfeh GdGbJUGOj, fTCI h JWhQ GdYhdeI GdeGdjI h YfGUQgG GdCSGSjI, YdGbI YfGUQ GdYhdeI GdeGdjI HGdfeh GdGbJUGOj, Gdgjcd GdGfJGLj h GdeGdj aj Ohd eLdS GdJYGhf GdNdjLj, Gdfeh GdGbJUGOj Hjf GdGYJeGO Ydi GdfaW h JfhjY eUGOQ GdONd, GdbWGY GdeUQaj aj Ohd eLdS GdJYGhf, hGbY h JWhQ CShGb GdeGd GdNdjLjI, GdGSJKeGQ GdCLfHj GdeHGTQ aj Ohd eLdS GdJYGhf GdNdjLj, efGN GdGSJKeGQ GdeHGTQ h JWhQGJg GdcejI, bjGS CKQ GdGSJKeGQ GdCLfHj GdeHGTQ Ydi Gdfeh GdGbJUGOj Ohd eLdS GdJYGhf ddaJQI (B1985 (3` (B2007s
(3HHdjhZQGajG(B: (3U(B.385 (3edGMb U(B.361 s
Keywords: (3GdEbJUGO GdOhdjs; (3GdJfejI GdEbJUGOjs; (3GdYhdeIs